Characteristics of the nasal mucosa of commercial pigs during normal development - Yuchen Li; Chengjie Yang; Yuqi Jiang; Xiuyu Wang; Chen Yuan; Jiaxin Qi; Qian Yang (Veterinary Research, 2023)
Abstract The nasal mucosa is constantly exposed to inhaled pathogens and is the first defence against respiratory infections. Here, we investigated the structural and compositional characteristics of the nasal mucosa of commercial pigs at various growth stages. The epithelial thickness, number of capillaries, and secretion function of the nasal mucosa dramatically increased with age; however, underlying lymphoid follicles in the respiratory region were rarely observed across the growth stages. The nasal mucosa was explored at the epithelial, immunological, and biological (commensal microbiota) barriers. In the epithelial barrier, the proliferative capacity of the nasal epithelia and the expression of tight junction proteins were high after birth; however, they decreased significantly during the suckling stage and increased again during the weaning stage. In the immunological barrier, most pattern recognition receptors were expressed at very low levels in neonatal piglets, and the innate immune cell distribution was lower. During the suckling stage, increased expression of Toll-like receptor (TLR) 2 and TLR4 was observed; however, TLR3 expression decreased. TLR expression and innate immune cell quantity significantly increased from the weaning to the finishing stage. In the biological barrier, Firmicutes, Actinobacteria, Proteobacteria, and Bacteroidetes comprised the dominant phyla in neonatal piglets. A dramatic decrease in nasal microbial diversity was observed during the suckling stage, accompanied by an increase in potentially pathogenic bacteria. Proteobacteria, Bacteroidetes, and Firmicutes were identified as the core phyla of the nasal microbiota; among these, the three dominant genera, Actinobacter, Moraxella, and Bergerella, may be opportunistic pathogens in the respiratory tract. These characteristics comprise an essential reference for respiratory infection prevention at large-scale pig farms.